Does COVID-19 vaccination affect risk perception and adherence to preventive behaviors? A systematic review and meta-analysis - Sorrentino, Michele; Fiorilla, Claudio; Rubba, Fabiana; Montuori, Paolo; Palladino, Raffaele (Frontiers in Public Health, 2025)
IntroductionSince the COVID-19 pandemic onset, preventive measures (e.g., social distancing, hand hygiene, mask usage) and vaccines have been pivotal in mitigating transmission and reducing public health burdens. Although adherence to these measures, influenced by factors such as ventilation and exposure duration, has been extensively validated, their long-term sustainability faces socio-economic challenges.ObjectivesTo investigate the association between risk perception and adherence to preventive behaviors and conduct a meta-analysis comparing these behaviors in vaccinated versus unvaccinated subgroups.MethodsA systematic review following PRISMA guidelines identified studies (2021–2024) analyzing risk perception and preventive behaviors. Potential biases were assessed using the MMAT tool. A meta-analysis calculated pooled effect sizes across subgroups.ResultsOf 1,594 screened studies, 10 met inclusion criteria (six for meta-analysis, n = 9,115). Populations included adults, students, and healthcare professionals across 24 countries. Most vaccinated individuals maintained preventive behaviors despite stable or declining risk perception, though social distancing and hand hygiene adherence decreased over time. Booster-vaccinated individuals exhibited higher compliance than partially vaccinated or unvaccinated counterparts. Unvaccinated individuals intending to vaccinate reported higher risk perception than those refusing vaccination. Meta-analysis revealed no significant difference in risk perception between vaccinated (70.3, 95% CI 60.8–79.8) and unvaccinated subgroups (70.8, 95% CI 61.9–79.6; I2 = 17.5%), suggesting limited influence on behavior maintenance.ConclusionWhile vaccination and preventive measures curbed COVID-19 transmission, risk perception alone does not robustly predict sustained adherence, potentially due to risk compensation. Future research should prioritize determinants of long-term behavioral retention in public health strategies.